The Church as Societas Perfecta in the Schemata of Vatican I - Granfield, Patrick 1930-2014 (1979)
Over the course of a century, the self-understanding of the Roman Catholic Church has undergone a dramatic change, as seen, for example, in the contrasting ecclesiologies of the last two ecumenical councils. The following juxtaposition of representative texts from Vatican I and Vatican II reveals this radical shift.